Inflammasomes in dendritic cells: Friend or foe? - Hatscher, Lukas; Amon, Lukas; Heger, Lukas; Dudziak, Diana (Immunology Letters, 2021)
Inflammasomes are cytosolic multiprotein complexes that crucially contribute to host defense against pathogens but are also involved in the pathogenesis of autoinflammatory diseases. Inflammasome formation leads to activation of effector caspases (caspase-1, 4, 5, or 11), the proteolytic maturation of IL-1β and IL-18 as well as cleavage of the pore-forming protein Gasdermin D. Dendritic cells are major regulators of immune responses as they bridge innate and adaptive immunity. We here summarize the current knowledge on inflammasome expression and formation in murine bone marrow-, human monocyte-derived as well as murine and human primary dendritic cells. Further, we discuss both, the beneficial and detrimental, involvement of inflammasome activation in dendritic cells in cancer, infections, and autoimmune diseases. As inflammasome activation is typically accompanied by Gasdermin D-mediated pyroptosis, which is an inflammatory form of programmed cell death, inflammasome formation in dendritic cells seems ill-advised. Therefore, we propose that hyperactivation, which is inflammasome activation without the induction of pyroptosis, may be a general model of inflammasome activation in dendritic cells to enhance Th1, Th17 as well as cytotoxic T cell responses.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Dendritic cell; Hyperactivation; Inflammasome; NLRP3; T cell response; Vaccination